2010
DOI: 10.1093/alcalc/agq052
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Demographic and Clinical Correlates of the Dimensions of Alcohol Use Behaviour

Abstract: Two main conclusions justify the two-factor approach to alcohol use classification. First, the model fit was considerably superior and, second, the dimensions of alcohol consumption and alcohol-related problems vary considerably in their associations with measures of demographic and clinical risk. A one-factor representation of alcohol use, for instance, would fail to recognize that measures of affective/anxiety disorders are more consistently related to alcohol-related problems than to alcohol consumption. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
3
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
2
13
3
5
Order By: Relevance
“…Using the total AUDIT score may obscure more complex relationships with socio-demographic and behavioural factors. This conclusion parallels that from other recent research that also emphasizes the need to look separately at multiple dimensions of the AUDIT when investigating issues of aetiology (Smith et al ., 2010). …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using the total AUDIT score may obscure more complex relationships with socio-demographic and behavioural factors. This conclusion parallels that from other recent research that also emphasizes the need to look separately at multiple dimensions of the AUDIT when investigating issues of aetiology (Smith et al ., 2010). …”
Section: Discussionsupporting
confidence: 87%
“…The only other study of AUDIT dimensions in relation to employment we have found was from the UK. This reported an association with employment status measured by economic activity and inactivity and the alcohol-related problems domain of the AUDIT but not the consumption domain (Smith et al ., 2010). However, studies using other measures of alcohol consumption patterns have shown higher levels of both alcohol consumption and problem drinking in men who are unemployed (Lee et al ., 1990; Montgomery et al ., 1998; Bobak et al ., 1999; Halme et al ., 2008; Virtanen et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also contrast with several other studies that support a two-factor model, with the first 3 items loading on a factor usually labeled as “alcohol consumption” and the remaining items loading on a second factor labeled “alcohol-related problems (Shields, Guttmannova, & Caruso, 2004; Smith, Shevlin, Murphy, & Houston, 2010). …”
Section: Discussioncontrasting
confidence: 61%
“…The 2 types of excessive drinking are each associated with serious health risks (World Health Organization, 2000) and with alcohol-related problems (Caetano et al, 2012;Gmel et al, 2001). Co-occurrence of both types of excessive drinking may point to a small but serious group of alcohol users with a severe problematic drinking pattern in itself (Smith et al, 2010). In the remainder of this article, excessive alcohol consumption (EAC) will refer to this combination of excessive drinking types.…”
mentioning
confidence: 99%